PENGARUH KLASIFIKASI TEMUAN PEMERIKSAAN DAN OPINI TAHUN SEBELUMNYA TERHADAP PENENTUAN OPINI PEMERIKSAAN BPK ATAS LAPORAN KEUANGAN PEMERINTAH DAERAH - Janu Hasnowo; Haryanto Haryanto (Diponegoro Journal of Accounting, 2016)
This research aims to prove empirically by explaining directly influence the classification of the audit findings (weakness of internal control systems and non-compliance with laws and regulations) and the previous year's audit opinion on the determination of the audit opinion from the Audit Board of Republic of Indonesia (BPK RI) on the financial statement of the local government (LKPD). The independent variable, weakness of the internal control system is proxied by the number of weaknesses ot the system of accounting and reporting controls, the number of weaknesses of the implementation of the control system of income and expenditure budget, and the weakness of the internal control structure. As for the independent variable, non-compliance with laws and regulations is proxied by the number of cases of loss of the local government, the number of cases of potential loss of the local goventment, the number of cases of shortage of income and the number of cases of administrative irregularities. Analysis of the data in this research using ordinal logistic regression, since the variable is proxied by ordinal data into WTP, WTP-DPP, WDP, TMP and TW. This research uses secondary data, audit reports of BPK on the financial statements of the local government from fiscal Year 2012 to 2013. The results of research shows that the weaknesses ot the system of accounting and reporting controls, and cases of loss of the local government negatively affect the determination of audit opinion on the financial statement of the local government, while the previous year’s audit opinion positively affect to these.